PENGEMBANGAN BAHAN BACAAN REFUTATION TEXT SEBAGAI MEDIA UNTUK MEREMEDIASI MISKONSEPSI MATERI USAHA DAN ENERGI - yarso, Sarinah; Maria S., Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to analyze and produce refutation-structured text handout to remediate student misconception on work and energy. Research and Development (R&D) method used in this study which was adopted from seven steps Borg & Gall development. It involved 96 students from 2 schools in Rasau Jaya whom participated in preliminary field and main field. Data collected by using validity questionnaire, student response questionnaire and diagnositc test. The results of data analysis showed that refutation-structure text handout material was suitable to use as a medium to remedy misconceptions about material aspects validity of 0.86 (very high criteria), language aspects 0.87 (very high criteria), and graphic aspects of 0.78 ( high criteria). Students' responses to the first field test obtained a percentage of 80.05% (very high category) and the main field test obtained an average percentage of 80.63% (very high category). The results of this study was expected could be used by teacher to remediate work and energy misconception as an alternative media. Keywords: Development, Refutation-Structured TextHandout, Work and energy